2011
DOI: 10.1007/s00359-010-0623-4
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of auditory saccular sensitivity in the plainfin midshipman fish, Porichthys notatus

Abstract: The auditory system of the plainfin midshipman fish, Porichthys notatus, is an important sensory receiver system used to encode intraspecific social communication signals in adults, but the response properties and function of this receiver system in pre-adult stages are less known. In this study we examined the response properties of auditory-evoked potentials from the midshipman saccule, the main organ of hearing in this species, to determine whether the frequency response and auditory threshold of saccular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 57 publications
3
21
1
Order By: Relevance
“…Our findings are in contrast to those reported from a study conducted in the batrachoidid P. notatus, which showed via saccular potential recordings that auditory threshold curves were similar throughout development (Alderks and Sisneros, 2011) (Fig. 4).…”
Section: Ontogenetic Development Of Peripheral Auditory Sensitivitycontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are in contrast to those reported from a study conducted in the batrachoidid P. notatus, which showed via saccular potential recordings that auditory threshold curves were similar throughout development (Alderks and Sisneros, 2011) (Fig. 4).…”
Section: Ontogenetic Development Of Peripheral Auditory Sensitivitycontrasting
confidence: 99%
“…Note that within Lusitanian toadfish, small juveniles differed significantly from large juveniles and adults, which revealed higher auditory sensitivity and produced the full vocal repertoire. In contrast, in the midshipman fish, the auditory sensitivity of different size groups is similar and vocal behaviour has only been detected in adults (based on Alderks and Sisneros, 2011). Number of animals and number of recordings per group are indicated in parentheses.…”
Section: Ontogenetic Development Of Peripheral Auditory Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures for exposing and recording from the inner ear saccule followed those used in previous studies (Sisneros 2007(Sisneros , 2009bAlderks and Sisneros 2011). Briefly, animals were initially anesthetized in a 0.025% ethyl-p-aminobenzoate/saltwater bath until the fish's opercula ceased movement for at least 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Popper and Fay (2011) proposed that all future fish hearing studies should independently characterize particle motion and sound pressure sensitivities of fish regardless of any hearing specializations that fish may possess (e.g., accessory hearing structures such as Weberian ossicles that connect the swim bladder to the inner ear). Previous auditory physiology studies of the plainfin midshipman fish have primarily reported auditory responses with regard only to sound pressure Bass 1999, 2001;Sisneros et al 2004;Bass 2003, 2005;Sisneros 2007Sisneros , 2009bAlderks and Sisneros 2011;Rohmann and Bass 2011; but for the exception see Weeg et al 2002). Thus, better characterization of particle motion sensitivity in this species and across the different sexual phenotypes is warranted.…”
Section: Introductionmentioning
confidence: 99%